Preparation and Properties of Dual-Network Upper Critical Solution Temperature-Type Deep Profile Control Slow-Swelling Particles - Logue, Kristen M.; Favela, Mary; Lennard, Calorin (Journal of Green Energy and Environmental Engineering, 2026)
A dual-network upper critical solution temperature (UCST)-type hydrogel, poly(methyl methacrylamide)/poly(N,N-dimethylacrylamide) (PMAAm/PDMAA), was prepared via free radical polymerization and a soaking method using methyl methacrylamide (MAAm) and N,N-dimethylacrylamide (DMAA) as monomers, N,N-methylene bisacrylamide (BIS) as a crosslinking agent, and 2,2-diethoxyacetophenone (I-2959) as an initiator, for application in profile control and water plugging. The morphology, hydrogen bonding interactions, and temperature-responsive properties of the hydrogel were characterized by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and a high-temperature rheometer. The swelling behavior in response to temperature and the influence of the ratio of hydrogen bond donors (amine groups) to hydrogen bond acceptors (carbonyl groups) on the mechanical properties of the hydrogel were investigated. The results showed that when the molar ratio of MAAm to DMAA was 2:1, the prepared dual-network UCST-type hydrogel (PMAAm/PDMAA-2.0) exhibited a high transition temperature (90 °C), a tensile strength of up to 13.8 MPa, a tensile strain at break of 100.9%, and a compressive strength of 4.0 MPa at 80% compressive strain. The UCST response of PMAAm/PDMAA-2.0 was primarily attributed to the association and dissociation of hydrogen bonds between polymer chains, which led to swelling resistance at low temperatures and significant water absorption and expansion (up to 40 times its original size) at high temperatures, with a breakthrough pressure of 0.65 MPa.